Supporting TPACK through Technology-Based Instructional Plan - Basori Basori (ELITE Association Indonesia, 2023)
ABSTRACTTechnological Pedagogical Content Knowledge (TPACK) is a framework teachers can follow to implement technology in the classroom. With the presence of technology, mastering English skills and language components is beyond possible. In listening, for instance, exposure to meaningful inputs is greater. With the help of technology, students can access to meaningful inputs for their listening. Students have many different options to listen to what is happening in the English-speaking world. At the same time, teachers are provided with abundant resources online that they can use or incorporate to assist them in teaching listening. The abundant technology eases teachers’ responsibility for creating a supportive teaching and learning environment. Hence, this practical article aims to present a unit plan that considers elements involved in designing instructions for teaching listening in the EFL context as the setting that involves technology integration. Among many online resources, the ESL-lounge is selected as listening material that is free to use, interesting and meaningful. The plan is designed to teach listening to university students, yet the outline suits all education levels and can be adapted to teach other skills and language components. Through appropriate lesson planning, teachers’ TPACK and professional development are strengthened. Keywords: TPACK; lesson plan; EFL/ESL context